Providing knowledge recommendations: an approach for informal electronic mentoring - Colomo-Palacios, Ricardo; Casado-Lumbreras, Cristina; Soto-Acosta, Pedro; Misra, Sanjay (Interactive Learning Environments, 2017)
The use of Web 2.0 technologies for knowledge management is invading the corporate sphere. The Web 2.0 is the most adopted knowledge transfer tool within knowledge intensive firms and is starting to be used for mentoring. This paper presents IM-TAG, a Web 2.0 tool, based on semantic technologies, for informal mentoring. The tool offers recommendations of mentoring contents built upon personal competencies of the mentee, combined with content and opinion tagging. To validate the tool, a case study comparing recommendations from the IM-TAG and a group of experts was conducted. Results show that the accuracy of IM-TAG's recommendations is notable and satisfactory. The main conclusions of this research may be valuable to organizations immersed in mentoring programs.
Keywords: organizational culture; web content analysis; informal mentoring; knowledge recommendations; mentoring; JCR; Scopus